2007
DOI: 10.1038/sj.bjp.0707460
|View full text |Cite
|
Sign up to set email alerts
|

The orphan receptor GPR55 is a novel cannabinoid receptor

Abstract: Background: The endocannabinoid system functions through two well characterized receptor systems, the CB 1 and CB 2 receptors. Work by a number of groups in recent years has provided evidence that the system is more complicated and additional receptor types should exist to explain ligand activity in a number of physiological processes. Experimental approach: Cells transfected with the human cDNA for GPR55 were tested for their ability to bind and to mediate GTPgS binding by cannabinoid ligands. Using an antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
1,491
11
21

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,385 publications
(1,553 citation statements)
references
References 51 publications
30
1,491
11
21
Order By: Relevance
“…GPR55 promotes cancer cell proliferation C Andradas et al pointing out that GPR55, as other members of the lysophospholipid GPCR families, exerts its actions, at least in part, through G 12/13 and G q proteins (Ryberg et al, 2007;Lauckner et al, 2008;Henstridge et al, 2009), which signal oncogenic effects (Dorsam and Gutkind, 2007;Worzfeld et al, 2008). It is therefore tempting to speculate that LPI, through GPR55, would behave similar to their close relatives lysophosphatidic acid and sphingosine-1-phosphate in terms of involvement in cancer biology.…”
Section: Gpr55 Promotes Cancer Cell Proliferationmentioning
confidence: 99%
See 3 more Smart Citations
“…GPR55 promotes cancer cell proliferation C Andradas et al pointing out that GPR55, as other members of the lysophospholipid GPCR families, exerts its actions, at least in part, through G 12/13 and G q proteins (Ryberg et al, 2007;Lauckner et al, 2008;Henstridge et al, 2009), which signal oncogenic effects (Dorsam and Gutkind, 2007;Worzfeld et al, 2008). It is therefore tempting to speculate that LPI, through GPR55, would behave similar to their close relatives lysophosphatidic acid and sphingosine-1-phosphate in terms of involvement in cancer biology.…”
Section: Gpr55 Promotes Cancer Cell Proliferationmentioning
confidence: 99%
“…Nonetheless, all the functions described so far for LPI on GPR55 come from experiments in which LPI was exogenously added to the cultured cells, and therefore evidence for the role of the naturally occurring lipid in more physiological settings is still missing. It has also been shown that several cannabinoid-type compounds modulate this receptor (Ryberg et al, 2007;Lauckner et al, 2008;WaldeckWeiermair et al, 2008;Henstridge et al, 2009Henstridge et al, , 2010Kapur et al, 2009;Yin et al, 2009). However, the inconsistencies among the pharmacological results obtained so far (some compounds being active in some reports and inactive in others, some being agonists in some studies and antagonists in others, and so on) do not entirely clarify whether GPR55 is an actual cannabinoid receptor (Brown and Robin Hiley, 2009;Ross, 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, two cannabinoid receptors have been identified by molecular cloning, CB 1 and CB 2 receptors (Howlett et al, 2002;Matsuda et al, 1990;Munro et al, 1993), however the existence of additional CB receptors have also been proposed (Brown, 2007;Pacher et al, 2005;Ryberg et al, 2007). Anandamide is a partial or full agonist of CB 1 receptors, depending on the tissue and biological response measured.…”
Section: Introductionmentioning
confidence: 99%